Portal Hypertensive Enteropathy in Liver Cirrhosis - Marcellus Simadibrata; Vera Yuwono; FJW Ten Kate; GNJ Tytgat; Daldiyono Daldiyono; Laurentius Lesmana; Iwan Ariawan (The Indonesian Society for Digestive Endoscopy, 2006)
Background/Aim: Some studies found that portal hypertension cause complication such as portal hypertensive gastroenterocolopathy. This study was done to find any abnormalities in the small intestinal mucosa and villi of the portal hypertensive patients. Method: Thirty patients with liver cirrhosis, portal hypertension and esophageal varices between 2000 - 2001 were included in this study. A duodenoscopic examination was performed to determine any abnormalities. Biopsy specimens were taken from the descending part of duodenum and the duodenal bulb for histopathological examination. The findings were compared to 37 functional dyspepsia patients. Result: In the duodenal bulb and descending part of duodenum: the width of the villous of the portal hypertensive group was larger than the control (p 0.001), the diameter of the mucosal villous vessel was larger than in the control (p 0.001) and the thickness of the mucosal villous vessel wall was thicker than in the control (p 0.001). Conclusion: There were abnormalities of the mucosa in portal hypertensive enteropathy patients including the mucosal vessel diameter, wall thickness, number of goblet cells. Keywords: portal hypertensive enteropathy, liver cirrhosis